The Impact of Technology on Islamic Workplaces - Natsir, Imron; Flores, Josefa; Fernandez, Carlos (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Technological advancements have significantly transformed workplace environments across various industries, including those operating within Islamic frameworks. The integration of digital tools, automation, and artificial intelligence (AI) in Islamic workplaces has reshaped organizational structures, work ethics, and employee interactions, raising questions about the compatibility of technology with Islamic business principles. Balancing efficiency, ethical considerations, and adherence to Islamic values presents both opportunities and challenges for organizations seeking to maintain Islamic ethical integrity in a rapidly evolving digital era. This study aims to examine the impact of technology on productivity, ethical work practices, and employee engagement in Islamic workplaces. A mixed-methods approach is employed, combining surveys distributed to employees in Islamic organizations and in-depth interviews with business leaders and Islamic scholars. Quantitative data measures changes in productivity and employee satisfaction, while qualitative data explores perceptions of ethical dilemmas, technological dependence, and alignment with Islamic work ethics. Findings indicate that while technology enhances operational efficiency and flexibility, concerns arise regarding digital distractions, ethical challenges in automation, and the erosion of traditional interpersonal workplace values. The study concludes that technology must be strategically implemented to support productivity without compromising Islamic ethical principles.